Immune cell surface functionalization strategies for potentiating cell-based therapy against solid tumors - Yuting Wang; Aizhu Liu; Zhuosen Liang; Ye Yun; Chiyu Jia; Yun-Long Wu; Zheng Luo (Chemical Engineering Journal, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Mitigation role of edible oil and polyol sweeteners in the formation of acrylamide and 5-hydroxymethylfurfural in baked bread - You Long; Feng Li; Yuting Wang; Qiang Yu; Jianhua Xie; Yi Chen (Food Control, 2026)

A fluorescent/photochromic dual-function Mo-based hydrogel for information encryption - Sha Long; Yanghang Liu; Jingxing Gui; Yuting Xue; Yuxuan Ma; Baojiang Liu; Chunyan Hu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Covalent organic frameworks for food contaminant detection: Applications and DFT calculations - You Long; Yuting Wang; Gan Zhang; Yichun Wang; Qiang Yu; Yi Chen (Trends in Food Science & Technology, 2026)

A ratiometric fluorescent probe with distinct response to Aflatoxin B1 and B2a: probe design, bioimaging, and quantification - Linhui Peng; Yuting Luo; Zhiqing Xun; Zhongyong Xu; Taoyuze Lv; Xinrong Du; Zhaohui Wang; Ya-Long Wang; Tianyi Qin; Bin Liu; Ming-Qiang Zhu (Food Chemistry, 2026)

Exploring the oasis of plant genomes: From genetic variations to function and beyond - Xu Han; Zhanxiang Zong; Weidong Ning; Yuting Zhang; Zengdong Tan; Yunhao Liu; Yukun Song; Qiyuan Long; Yuyan Xiang; Shaoping Lu; Xuan Yao; Hu Zhao; et al. (Molecular Plant, 2026)

Coordinate fixed and mobile charging station deployment and scheduling for fluctuating demand - Chen Peng; Yang Yang; Enjian Yao; Long Pan; Yuting Zhu (Transportation Research Part D: Transport and Environment, 2026)

Nanoscale insights into cellulose–imidazolium ionic liquid interactions via atomic force microscopy - Ruimei Cao; Hongshuai Gao; Wanxue Lv; Yuting Song; Yan Long; Min Yu; Baozeng Ren; Yi Nie; Suojiang Zhang (Carbohydrate Polymers, 2026)

Combinatorial engineering of Saccharomyces cerevisiae for high level production of astaxanthin - Yuting Shi; Yanmei Li; Jiaheng Liu; Dongxu Chen; Xianhao Xu; Zhendong Li; Yanfeng Liu; Guocheng Du; Jianghua Li; Jian Chen; Xueqin Lv; Long Liu (Systems Microbiology and Biomanufacturing, 2026)

Decoding volatile compound-aroma attribute correlations in representative Oolong Teas of Fujian: An integrated objective quantification and GC–MS profiling method - Chengzhe Zhou; Jiaxin Fang; Shuaibo Shao; Cheng Zhang; Caiyun Tian; Zhengdong Zhang; Anru Zheng; Yuting Li; Siwei Deng; Changlian Wu; Shengjing Wen; Nadang Long; et al. (Food Chemistry, 2026)

Cell wall remodeling mediated banana-Bacillus velezensis interaction determines banana health during Foc 1 infection - Shazma Gulzar; Yaxin Xu; Zan Yi; Rahat Sharif; Zhihui Long; Yuting Weng; Yisha Lu; Huiling Zhan; Yihua Tan; Zhen Liu; Chunxiang Xu (Pesticide Biochemistry and Physiology, 2026)

Smartphone app-enabled dual-mode fluorescence and colorimetric portable sensors using RB@BSA-AuNRs for quality identification of plant-derived products - Hengye Chen; Xueqing Zeng; Guanghua Lei; Yun Huang; Wanjun Long; Wei Lan; Yuting Guan; Haiyan Fu (Food Research International, 2026)

Enhancing the functional properties of egg yolk through post-treatments following short-term fermentation for application in powdered oils - Junlin Ge; Qiuyu Ye; Daping Long; Jiajing Liu; Yuting Ye; Jiawen Pei; Xuebo Liu; Xiang Duan (Food Research International, 2026)

Magnetic covalent organic framework with theory calculation coupled to UPLC-MS/MS for selective enrichment and simultaneous quantification of seven emerging mycotoxins in wheat - You Long; Yuting Wang; Gan Zhang; Bei Gan; Qiang Yu; Jianhua Xie; Xinyi Zang; Yi Chen (Food Chemistry, 2026)

Flavor modulation of braised He Bao carp (Cyprinus carpio) by natural plant spices: Insights from GC–MS, GC–IMS, E-nose, E-tongue, and molecular docking analyses - Yuwei Liu; Yuting Wang; Ziyi Liu; Chang Li; Qiang Yu; Jianhua Xie; You Long; Qianzhu E; Yi Chen (Food Bioscience, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Lipid–sugar conversion regulates early white clover (Trifolium repens) seedling establishment under cadmium stress - Yuting Wu; Long Lin; Wanlin Ni; Yankang Zhang; Qinghuang Li; Zhou Li (Planta, 2026)

Characterization and bioaccessibility of Fe2+-oat bran peptide chelate - Wanhong Jin; Liang Wang; Qin Ma; Yuting Zhang; Long Yang; Xiaoya Wang; Dunhua Liu (Food Chemistry, 2025)

Differential microbial responses enhance soil organic carbon under long-term nitrogen fertilization - Ding Wang; Guangqiang Long; Hailin Zhang; Jie Wang; Yuting Zhang; Xinping Chen; Xiaojun Shi (Plant and Soil, 2025)

Cortical contribution related to top-down regulation in tone perception - Xiaotong Zhang; Yuting Tang; Houmin Wang; Zijian Huang; Wahou Tai; Soitou Wong; Zhuoming Chen; Jinyi Long (Cognitive Neurodynamics, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Modulation of electronic structure caused by the coupling between Al, P modified NiO and Ru for boosting alkaline hydrogen evolution - Yuhao Yin; Yao Zhu; Long Qian; Fei Wang; Ziyu Yuan; Yuting Dai; Tao Zhang; Dongya Yang; Fengxian Qiu (Fuel, 2025)

A numerical study of the morphodynamic response of reef islands under spectral waves - Yu Yao; Yuting Song; Long Chen; Changshen Li (Continental Shelf Research, 2025)

Deoxynivalenol as a cross-contaminant in foods: Simultaneous detection, combined toxicity, and sustainable mitigation technologies - Jiawen Lu; You Long; Xingtao Zhou; Yuting Wang; Qiang Yu; Chang Li; Doris Marko; Yi Chen (Food Bioscience, 2025)

Three-dimensional morphodynamic modeling of reef islands in response to climate change - Yu Yao; Min Kuang; Zhongwei Zhao; Yuting Song; Long Chen (Estuarine, Coastal and Shelf Science, 2025)

A nanozyme colorimetric sensor combined with cloud-based machine learning algorithm-assisted WeChat mini program for intelligent identification of Chinese green tea - Wanjun Long; Siyu Wang; Yangcheng Ling; Yuting Guan; Huiru Zhang; Hengye Chen; Wei Lan; Yuanbin She; Haiyan Fu (Food Research International, 2025)

Interaction and driving factors influencing microplastics and dissolved organic matter in the hyporheic ecosystem of the Jinghe River Basin under different land-use types - Yuting Zhang; Bingjie Li; Zeyu Chen; Jiayuan Feng; Jinxi Song; Yongqing Long; Myint Myint Nyein; Bawa Precious Tani; Mengyang Yang (Journal of Hazardous Materials, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Gut microbiota mediated immunoregulatory effects of Dendrobium officinale polysaccharides-selenium nanoparticles complexes - Yan Long; Jiajing Yang; Hongfei Ji; Yuting Fan; Keyao Dai; Wenjie Ding; Haiyu Ji; Juan Yu (Food Bioscience, 2025)

Field effect and coupling influences of urban park cold islands under varying wind speeds and heat island gradients - Chunyu Li; Yu Zhang; Hong Liang; Yang Yu; Siyu Long; Yuting Sun; Tong Wang; Kai Wang; Qian Cao (Urban Climate, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Association between exposure to brominated flame retardants and atherosclerosis: Evidence for inflammatory status as a potential mediator - Zihui Zhao; Chi Zhang; Yuanyuan Li; Junli Liu; Liangao Wang; Xianhao Wang; Yiqian Wang; Meng Liu; Xianfeng Yue; Xiaoyan Wang; Yuting Wang; Long Ji; et al. (Science of The Total Environment, 2025)

Coexistence of episodic and prolonged magmatism during the exhumation of subducted continental crust revealed by multi-method chronology of Early Paleozoic granites in South Altyn, western China - Long Tian; Lei Kang; Liang Liu; Danling Chen; Yuting Cao; Yongsheng Gai; Tuo Ma (Journal of Asian Earth Sciences, 2025)

Improvement of the gel properties of curdlan gel by hydrogen bonding interaction with trehalose - Long-Qing Li; Le-Yi Pan; Tong-Xin Liang; Mingyu Jin; Ya-Hui Yu; Xiangying Yu; Xiaozhen Liu; Fengyuan Liu; Yuting Li; Jing-Kun Yan (Food Hydrocolloids, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Interaction and bacterial effects of microplastics pollution on heavy metals in hyporheic sediments of different land-use types in the Beiluo River Basin - Bingjie Li; Zeyu Chen; Yuting Zhang; Ruichen Mao; Jinxi Song; Yongqing Long; Bin Tang; Jiayuan Feng; Myint Myint Nyein (Environmental Pollution, 2025)

Biomineralization-inspired functional biomaterials: From principles to practice - Haohua Hu; Yuting Lin; Bin Yang; Xiaoqing Wen; Panqin Ma; Xian Jun Loh; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Multiscale cellulose-based optical management films with tunable transparency and haze fabricated by different bamboo components and mechanical defibrillation approaches - Yu Chen; Yuting Zhang; Juan Long; Kaimeng Xu; Tuhua Zhong (Carbohydrate Polymers, 2025)

Corrigendum to ‘A facile synthesis of Ag3PO4/BiPO4 p-n heterostructured composite as a highly efficient photocatalyst for fluoroquinolones degradation’ [Environ. Res. 203 (2022) 111843] - Xin Zhu; Yu Yan; Yuting Wang; Tao Long; Jinzhong Wan; Cheng Sun; Yang Guo (Environmental Research, 2024)

MnCe-based catalysts for removal of organic pollutants in urban wastewater by advanced oxidation processes - A critical review - Yuting Wang; Jiaqing Wang; Zeqing Long; Zhi Sun; Longyi Lv; Jinsong Liang; Guangming Zhang; Pengfei Wang; Wenfang Gao (Journal of Environmental Management, 2024)

Lamellar Ti3C2 MXene composite decorated with platinum-doped MoS2 nanosheets as electrochemical sensing functional platform for highly sensitive analysis of organophosphorus pesticides - Fei Wang; Yao Zhu; Long Qian; Yuhao Yin; Ziyu Yuan; Yuting Dai; Tao Zhang; Dongya Yang; Fengxian Qiu (Food Chemistry, 2024)

Insomnia and stress: the mediating roles of frontoparietal network - Miao He; Yuan Li; Mengting Chen; Huiyun Li; Chunrong Liang; Yanli Chen; Chunyan Long; Yuting Yang; Jingyi Ye; Yu Mao; Yan Wang; Ling Li (Brain Imaging and Behavior, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

A colorimetric sensor based on 4-MPBA Au@AgNPs for accurately identification of EnshiYulu tea grade - Yuting Guan; Siyu Wang; Guanghua Lei; Zikang Hu; Hengye Chen; Huiwen Gu; Xiaoli Yin; Yuanbin She; Wanjun Long; Haiyan Fu (Food Chemistry, 2024)

Phelligridimer A enhances the expression of mitofusin 2 and protects against cerebral ischemia/reperfusion injury - Xing Li; Bingtian Xu; Lu Long; Yuting Li; Xuan Xiao; Shuqin Qiu; Jiangping Xu; Li-Wen Tian; Haitao Wang (Chemico-Biological Interactions, 2024)

Exploring correlations between soy sauce components and the formation of thermal contaminants during low-salt solid-state fermentation - Feng Li; Yuting Wang; Hongxia Liao; You Long; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2024)

Selective reduction of chlorite to chloride in drinking water by UV/sulfite system: pathways, mechanisms, and kinetics - Qian Xiao; Yuting Duan; Hongyu Dong; Shuili Yu; Xingli Ji; Guicai Liu; Rongsheng Ning; Mingce Long (Chemical Engineering Journal, 2024)

Overexpression of Nrf2 reverses ferroptosis induced by Arenobufagin in gastric cancer - Jiao Long; Wenjun Wang; Jing Chu; Yueyue Li; Meng Wang; Jingjing Su; Yuting Yang; GuoKai Wang; Qinglin Li; Hui Cheng (Toxicology and Applied Pharmacology, 2024)

Source identification and exposure risk management for soil arsenic in urban reclamation areas with high background levels: A case study in a coastal reclamation site from the Pearl River Delta, China - Meng Chen; Yuting Zhang; Wenbing Ji; Qiang Chen; Yan Li; Tao Long; Lei Wang (Journal of Hazardous Materials, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

Overexpression of MbICE3 increased the tolerance to cold and drought in lettuce (Lactuca sativa L.) - Yangfan Wei; Zhenghao Li; Long Lv; Qian Yang; Zhi Cheng; Jiaqi Zhang; Wenhao Zhang; Yuting Luan; Aocheng Wu; Wenhui Li; Deguo Han (In Vitro Cellular & Developmental Biology - Plant, 2023)

Classification of Chinese traditional cereal vinegars and antioxidant property predication by fluorescence spectroscopy - Wanjun Long; Guanghua Lei; Yuting Guan; Hengye Chen; Zikang Hu; Yuanbin She; Haiyan Fu (Food Chemistry, 2023)

Optimization and kinetic analysis of direct acid leaching of vanadium from converter vanadium slag under atmospheric pressure - Yuting Xiong; Ling Wang; Long Wang; Shen Li; Guohua Yang; Chong Cao; Shuxian Liu; Yimiao Nie; Lanbo Jia (Minerals Engineering, 2023)

Ratiometric near-infrared upconversion fluorescence sensor for selectively detecting and imaging of Al3+ - Caiping Ding; Yuting Gu; Weiwei Chen; Long Chen; Longhua Guo; Youju Huang (Analytica Chimica Acta, 2023)

Long-term plastic mulching decreases rhizoplane soil carbon sequestration by decreasing microbial anabolism - Yüze Li; Yuting Hou; Quanming Hou; Mei Long; Yali Yang; Ziting Wang; Yuncheng Liao (Science of The Total Environment, 2023)

Root exudation processes induce the utilization of microbial-derived components by rhizoplane microbiota under conservation agriculture - Yüze Li; Mei Long; Yuting Hou; Wei Li; Xiaoliang Qin; Baogang Zhang; Tao Wen; Yongxing Cui; Ziting Wang; Yuncheng Liao (Soil Biology and Biochemistry, 2023)

Soil antibiotic resistance genes accumulate at different rates over four decades of manure application - Yuting Zhang; Xiying Hao; Ben W. Thomas; Tim A. McAllister; Matthew Workentine; Long Jin; Xiaojun Shi; Trevor W. Alexander (Journal of Hazardous Materials, 2023)

Partial melting of subducted continental crust during the exhumation: Insights from Palaeozoic granitic rocks in South Altyn, western China - Long Tian; Lei Kang; Liang Liu; Danling Chen; Chao Wang; Yuting Cao; Yongsheng Gai; Tuo Ma (Journal of Asian Earth Sciences, 2023)

A spectral learning path for simultaneous multi-parameter detection of water quality - Zhiqiang Guo; Fenli Liu; Qiannan Duan; Wenjing Wang; Qianru Wan; Yicai Huang; Yuting Zhao; Lu Liu; Yunjin Feng; Libo Xian; Hang Gao; Yiwen Long; et al. (Environmental Research, 2023)

Transcriptome analysis reveals the mechanisms of hepatic injury caused by long-term environmental exposure to atrazine in juvenile common carp (Cyprinus carpio L.) - Jingbo Liu; Guangcheng Yang; Yanxia Gao; Xinran Li; Yuting Long; Shuling Wei; Yuxin Zhao; Shanshan Sun; Shujuan Gao (Environmental Science and Pollution Research, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

Integrated biomarker parameters response to the toxic effects of high stocking density, CuSO4, and trichlorfon on fish and protective role mediated by Angelica sinensis extract - HuaTao Li; YuTing Ma; Ying Liu; Min Wu; Jiao Long; XiaoQin Jing; SiShun Zhou; Ping Yuan; Jun Jiang (Fish Physiology and Biochemistry, 2020)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Generation of obese rat model by transcription activator-like effector nucleases targeting the leptin receptor gene - Yuting Chen; Wenqing Lu; Na Gao; Yi Long; Yanjiao Shao; Meizhen Liu; Huaqing Chen; Shixin Ye; Xueyun Ma; Mingyao Liu; Dali Li (Science China Life Sciences, 2017)
The laboratory rat is a valuable mammalian model organism for basic research and drug discovery. Here we demonstrate an efficient methodology by applying transcription activator-like effector nucleases (TALENs) technology to generate Leptin receptor ( Lepr ) knockout rats on the Sprague Dawley (SD) genetic background. Through direct injection of in vitro transcribed mRNA of TALEN pairs into SD rat zygotes, somatic mutations were induced in two of three resulting pups. One of the founders carrying bi-allelic mutation exhibited early onset of obesity and infertility. The other founder carried a chimeric mutation which was efficiently transmitted to the progenies. Through phenotyping of the resulting three lines of rats bearing distinct mutations in the Lepr locus, we found that the strains with a frame-shifted or premature stop codon mutation led to obesity and metabolic disorders. However, no obvious defect was observed in a strain with an in-frame 57 bp deletion in the extracellular domain of Lepr . This suggests the deleted amino acids do not significantly affect Lepr structure and function. This is the first report of generating the Lepr mutant obese rat model in SD strain through a reverse genetic approach. This suggests that TALEN is an efficient and powerful gene editing technology for the generation of disease models.